Optimization of catalytic active sites in non-collinear antiferromagnetic Mn3Pt bulk single-crystal. (August 2019) - Li, G.; Yang, Q.; Manna, K.; Fu, C.; Deniz, H.; Jena, J.; Li, F.; Parkin, S.; Auffermann, G.; Sun, Y.; Felser, C.
Abstract: Electrons in non-collinear antiferromagnets exhibit abundant transfer properties of interest to next-generation innovative devices. As two of the most important properties of electrons, both charge and spin must be simultaneously transferred. This will certainly influence many surface reaction processes like the hydrogen evolution reaction (HER). We grow a Mn3 Pt bulk single-crystal that having a room-temperature long-range magnetic order at the Mn sites, which showed Pt-like activity and excellent stability as a catalyst for HER. Experiments and density-functional-theory calculations reveal that the electronic structure can be modified owing to the spin polarization of the Mn atoms. This further affects the adsorption energy of the reaction intermediate by tailoring the arrangement and filling of d-electrons. With this strategy, a similar Gibbs free energy for hydrogen adsorption was obtained between Mn–Mn hollow sites and Pt sites. In other words, more actives sites beyond Pt are created. This study paves the way for the design of high-efficiency electrocatalysts through the interplay between the spin states and the adsorption-desorption behaviors. Graphical abstract: Image 1 Highlights: High-quality Mn3 Pt bulk single crystals with defined crystal surface are synthesized. The single-crystal electrocatalyst showed outstanding hydrogen evolution reaction performance with ultra-small surface area. Theoretical calculations uncovered the importance of local magnetic moments on adsorption energy.